Supervised Speaker Diarization Using Random Forests: A Tool for Psychotherapy Process Research - Fürer, Lukas; Schenk, Nathalie; Roth, Volker; Steppan, Martin; Schmeck, Klaus; Zimmermann, Ronan (Frontiers in Psychology, 2020)
Speaker diarization is the practice of determining who speaks when in audio recordings. Psychotherapy research often relies on labor intensive manual diarization. Unsupervised methods are available but yield higher error rates. We present a method for supervised speaker diarization based on random forests. It presents a compromise between commonly used labor-intensive manual coding and fully automated procedures. The method is validated using the EMRAI synthetic speech corpus with the goal to examine the feasibility of later use on naturalistic data and is made available. It yields low diarization error rates (M: 5.61%, STD: 2.19). Supervised speaker diarization is a promising method for psychotherapy research and similar fields.